Supplementary motor area is deactivated during mental rotation tasks with biomechanical constraints in fMRI - Nomura, Makoto; Koeda, Michihiko; Ikeda, Yumiko; Tateno, Amane; Arakawa, Ryosuke; Aoyagi, Yoichiro (Frontiers in Human Neuroscience, 2024)
Mental rotation (MR) tasks of body parts involve anatomically interconnected brain systems. The systems are implicated in sensorimotor information integration and activate cortical motor-related areas, corresponding to the execution of similar motor tasks. In this study, we aimed to investigate the effect of varying the angle in the hand MR task on cerebral activation of the motor-related areas. Twenty healthy right-handed participants were recruited. We investigated cerebral activation while each participant decided whether a hand-palm image, rotated by 0°, 90°, 180°, and 270°, was a right or left hand. A significant negative correlation between the angle and brain activity was observed in the right and left supplementary motor area (SMA) and right posterior anterior cingulate gyrus. The SMA was inactivated with 180°- or 270°-rotated images in the regions of interest analysis. 180 °- and 270°-rotated palms would be biomechanically difficult to position; thus, SMA deactivation may be closely associated with biomechanical constraints. This study provided novel findings regarding the neurophysiological mechanisms of motor imagery and may be useful in developing treatment plans using MR tasks during patient rehabilitation.